Genetic evidence for adaptation-driven incipient speciation of Drosophila melanogaster along a microclimatic contrast in “Evolution Canyon,” Israel - Michalak, Pawel (The National Academy of Sciences, 2001)
Substantial genetic differentiation, as great as among species, exists between populations of Drosophila melanogaster inhabiting opposite slopes of a small canyon. Previous work has shown that prezygotic sexual isolation and numerous differences in stress-related phenotypes have evolved between D. melanogaster populations in “Evolution Canyon,” Israel, in which slopes 100–400 m apart differ dramatically in aridity, solar radiation, and associated vegetation. Because the canyon's width is well within flies' dispersal capabilities, we examined genetic changes associated with local adaptation and incipient speciation in the absence of geographical isolation. Here we report remarkable genetic differentiation of microsatellites and divergence in the regulatory region of hsp70Ba which encodes the major inducible heat shock protein of Drosophila, in the two populations. Additionally, an analysis of microsatellites suggests a limited exchange of migrants and lack of recent population bottlenecks. We hypothesize that adaptation to the contrasting microclimates overwhelms gene flow and is responsible for the genetic and phenotypic divergence between the populations.